2017
DOI: 10.1002/anie.201611371
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Giant Modular PKSs Provides Insight into Genetic Mechanism for Structural Diversification of Aminopolyol Polyketides

Abstract: Polyketides form many clinically valuable compounds. However, manipulation of their biosynthesis remains highly challenging. An understanding of gene cluster evolution provides a rationale for reprogramming of the biosynthetic machinery. Herein, we report characterization of giant modular polyketide synthases (PKSs) responsible for the production of aminopolyol polyketides. Heterologous expression of over 150 kbp polyketide gene clusters successfully afforded their products, whose stereochemistry was establish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
125
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 126 publications
(137 citation statements)
references
References 40 publications
6
125
1
3
Order By: Relevance
“…From this analysis it is apparent that KSs downstream of ACPs from the same module type clade with one another and that KSs upstream of ACPs from the same module type do not, with the expected exception of those in the first module of a bimodule . This analysis supports the redefinition of trans ‐AT PKS modules such that ACPs are grouped with the KSs downstream of them …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From this analysis it is apparent that KSs downstream of ACPs from the same module type clade with one another and that KSs upstream of ACPs from the same module type do not, with the expected exception of those in the first module of a bimodule . This analysis supports the redefinition of trans ‐AT PKS modules such that ACPs are grouped with the KSs downstream of them …”
Section: Resultsmentioning
confidence: 99%
“…From the sequencing of the erythromycin synthase in 1990 until last year, the boundaries of the modules of cis ‐AT assembly lines were incorrectly defined—comparisons with the domain organization of the mammalian FAS had led to the module being defined with KS at its upstream boundary and ACP at its downstream boundary. The processing enzymes in several cis ‐AT assembly lines have been shown to evolutionarily co‐migrate with the KS downstream of them, leading to the redefinition of cis ‐AT modules as possessing a downstream KS . When trans ‐AT assembly lines started to be discovered 15 years ago, often from difficult‐to‐culture, symbiotic bacteria, the use of cis ‐AT nomenclature resulted in their modules being incorrectly defined as well .…”
Section: Introductionmentioning
confidence: 99%
“…[1] Very recently, Abe and co-workers reported that the groups of domains that genetically migrate together during the evolution of PKS assembly lines do not match this definition. [2] …”
mentioning
confidence: 99%
“…5,1618 The SorPS9 active site contains a histidine and an asparagine at positions equivalent to those of the catalytic histidine and active site aspartate of DHs. Functional assays of SorPS9 point mutants with trans - α/β -unsaturated, ζ-hydroxyacyl NAC thioester substrates reveal the critical activity of the histidine and the ancillary role of the neighboring asparagine.…”
mentioning
confidence: 99%